Agribusiness Value Chains and Smallholder Empowerment: A Global Systematic Review - Hasna Maheswari; Raditya Setiawan (Arthatama: Journal of Business Management and Accounting, 2025)
This systematic literature review examines strategic approaches in value-added agriculture designed to enhance the economic returns of primary agricultural products. Adopting the PRISMA framework, the study utilizes the Watase Uake tool systematically screen and analyze literature. Six empirical and conceptual studies were published between 2022 and 2025 form the basis of our analysis, encompassing diverse contexts. Key themes include agribusiness intervention models, inclusive innovation mechanisms, integration into Global Value Chains (GVCs), and targeted capacity-building initiatives for smallholder farmers. Four principal strategic approaches emerge: the adoption of Porter’s Diamond model to assess national competitiveness, targeted value-chain interventions to improve product differentiation, systems-based innovations to foster cross-sector collaboration, and collective action frameworks to capture and distribute value equitably. We further synthesize critical enablers and barriers impacting strategy implementation across regions such as MENA, sub-Saharan Africa, and other developing countries. The review concludes by discussing theoretical contributions and practical implications and suggesting future research avenues, including the deployment of digital technologies, enhanced stakeholder collaboration, and supportive policy frameworks to maximize value addition.